PENGARUH MODEL PROBLEM BASED INSTRUCTION (PBI) TERHADAP KEMAMPUAN PENALARAN MATEMATIS - Ahde Fitri; Sukur (Mat-Edukasia, 2020)
This study aims to identify and describe mathematical reasoning abilities using the problem based instruction (PBI) model which is better than conventional learning for grade VI students of SD Negeri 115 / VI Bangko VIII. The method used is an experimental method. Sampling using simple random sampling technique. The instrument used in this research is a mathematical reasoning ability test in the form of a description. From the data analysis, it was concluded that the mathematical reasoning ability of students using the Problem Based Instruction (PBI) model was higher than the mathematical reasoning abilities of students who used conventional learning, the mathematical reasoning abilities of students with high initial abilities who took the Problem Based Instruction (PBI) model were not higher than students' mathematical reasoning using conventional learning, the mathematical reasoning abilities of students with low initial abilities who took part in learning with the PBI model were not higher than students' mathematical reasoning abilities using conventional learning, there was no interaction between learning models and students' initial abilities to influence students' mathematical reasoning abilities.